Concentrações plasmáticas de cortisol, hormônios tiroídeanos, metabólitos lipídicos e temperatura corporal de cabras alpinas submetidas ao estresse térmico - Uribe-Velásquez, Luis Fernando [UNESP]; Oba, Eunice [UNESP]; De Albuquerque Brasil, Lucia Helena [UNESP]; Wechsler, Francisco Stéfano [UNESP]; Mendonça Stachissini, Anee Valéria [UNESP] (My University, 1998)
The objective of this work was to determine the plasma concentrations of cortisol, thyroid hormone, lipids metabolites and corporal temperature of lactating Alpine goats submitted to heat stress. Six lactating Alpine goats were allotted randomly in a crossover experimental design for two groups: thermoneutral conditions or thermal stress. An adaptation period of 28 days was followed by four-periods of 14 days each, when the animals submitted to thermal stress were exposed to the average temperature of 33.84°C; THI of 86.20; BGT of 36.18 and BT of 32.11°C from 8:00 am to 5:00 pm, including simulated solar radiation from 10:00 am to 3:00 pm. There were no differences between the groups in the plasma concentrations of cortisol, thyroid hormones (T3- triiodothyronine and T-4tiroxine), and lipid metabolites (cholesterol and HDL). Rectal temperature was higher during thermal stress when compared to the group of animals in thermoneutral conditions. The goats maintained the thyroid plasma hormone concentrations, when exposed to repeated and intermittent stress, in spite of the occurrence of hypertermia during heat stress.
Plasma concentrations of cortisol, thyroid hormone, lipids metabolites and corporal temperature of lactating alpine goats submitted to heat stress
Keywords: Cortisol; Goats; Lipids metabolites; Radiation; Rectal temperature; Thyroid hormones